2012
DOI: 10.1103/physrevlett.109.248107
|View full text |Cite
|
Sign up to set email alerts
|

Small-Number Effects: A Third Stable State in a Genetic Bistable Toggle Switch

Abstract: A genetic toggle switch was studied experimentally and theoretically. We have found an additional kinetic stable state where all the genes express very lowly, which is predicted to be unstable by dynamical systems theory. It can also stably coexist with the other two known stable states, although this coexistence is forbidden in a deterministic dynamical system. We analyze that this nontrivial phenomenon results from the discrete and fluctuate nature in such a small system, by comparing experimental results wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…This small molecule number leads to non-negligible fluctuations and a discrete nature of molecular concentrations, which may in turn alter the frequencies of each chemical reaction event; indeed, several salient phenomena induced by the smallness in molecule numbers have been studied, both theoretically [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimentally. [17][18][19] Moreover, how such microscopic molecular discreteness can contribute to cellular functions at a larger scale has gathered much interest, and the effect induced by the discreteness is expected to provide a novel concept to understand cellular behaviors and function. 17,18,[20][21][22] In a macroscopic system, i.e., when the volume size of a system and the number of contained molecules are large, the overall behaviors of the system can be described by the deterministic rate equation of reaction dynamics for the average concentration of chemicals or a Langevin equation that takes into account small Gaussian fluctuation around it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This small molecule number leads to non-negligible fluctuations and a discrete nature of molecular concentrations, which may in turn alter the frequencies of each chemical reaction event; indeed, several salient phenomena induced by the smallness in molecule numbers have been studied, both theoretically [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimentally. [17][18][19] Moreover, how such microscopic molecular discreteness can contribute to cellular functions at a larger scale has gathered much interest, and the effect induced by the discreteness is expected to provide a novel concept to understand cellular behaviors and function. 17,18,[20][21][22] In a macroscopic system, i.e., when the volume size of a system and the number of contained molecules are large, the overall behaviors of the system can be described by the deterministic rate equation of reaction dynamics for the average concentration of chemicals or a Langevin equation that takes into account small Gaussian fluctuation around it.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Moreover, how such microscopic molecular discreteness can contribute to cellular functions at a larger scale has gathered much interest, and the effect induced by the discreteness is expected to provide a novel concept to understand cellular behaviors and function. 17,18,[20][21][22] In a macroscopic system, i.e., when the volume size of a system and the number of contained molecules are large, the overall behaviors of the system can be described by the deterministic rate equation of reaction dynamics for the average concentration of chemicals or a Langevin equation that takes into account small Gaussian fluctuation around it.…”
Section: Introductionmentioning
confidence: 99%
“…The dramatic failure of this prediction (the black areas are highly asymmetrical and extend around the bistable zone (Fig. 3c)) signals that either convergence to the local steady state(s) is drastically slowed down (for example, by a catastrophic slowdown 37 ) or even arrested (for example, by small number effects 38 ), or that an alternative stable state emerges from an unsuspected mechanism 39 . In any case, these trapped states could provide alternative options for memories on practical time scales.…”
Section: Resultsmentioning
confidence: 96%
“…However, Lipshtat et al found that stochastic effects can give rise to bistability even without cooperativity [32]. In another study, Ma et al found that stochastic fluctuations can stabilize the unstable steady state in the deterministic system, giving rise to tristability [33]. In addition, Biancalani et al identified multiplicative noise as the source of bistability in the stochastic case [34].…”
Section: Introductionmentioning
confidence: 99%